2011
DOI: 10.1186/1752-1947-5-543
|View full text |Cite
|
Sign up to set email alerts
|

One-stage laparoscopic-assisted resection of gastrojejunocolic fistula after gastrojejunostomy for duodenal ulcer: a case report

Abstract: IntroductionGastrojejunocolic fistula is a rare condition after gastrojejunostomy. It was thought to be a late complication related to stomal ulcers as a result of inadequate gastrectomy or incomplete vagotomy. We report a case of gastrojejunocolic fistula after gastrojejunostomy for peptic ulcer treated with one-stage laparoscopic resection.Case presentationA 41-year-old Japanese man complained of diarrhea for 10 months, as well as severe weight loss and weakness. After admission, we immediately started intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Several reports have shown gastrojejunocolic fistula to be a complication of partial gastrectomy and gastrojejunostomy with Billroth II (B-II) reconstruction (3,4). To our knowledge, this is the first report of DCF caused by a stomal ulcer developing 30 years after distal gastrectomy with B-I reconstruction.…”
Section: Introductionmentioning
confidence: 76%
“…Several reports have shown gastrojejunocolic fistula to be a complication of partial gastrectomy and gastrojejunostomy with Billroth II (B-II) reconstruction (3,4). To our knowledge, this is the first report of DCF caused by a stomal ulcer developing 30 years after distal gastrectomy with B-I reconstruction.…”
Section: Introductionmentioning
confidence: 76%
“…Modern management of GJF is via a one-stage resection. Masashi Takemura and all have concluded that today, laparoscopic-assisted one-stage en bloc resection may be feasible for patients with GJC fistula [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gastrojejunocolic fistula (GJCF) is a rare and late complication of gastrojejunostomy applied for recurrent peptic ulcer disease [1] . It was thought to be induced by a stomal ulcer, due to inadequate gastrectomy or incomplete vagotomy [1] , [2] . The symptoms in these situations include upper abdominal pain, weight loss, diarrhea, gastrointestinal bleeding, and fecal vomiting [3] .…”
Section: Introductionmentioning
confidence: 99%
“…These patients are cachectic and dehydrated, with labs showing malnutrition. Barium upper gastrointestinal series (UGIS), gastroscopy, and colonoscopy are used for diagnosis [1] . Although the occurrence of GJCF has decreased remarkably as a result of better treatment, the modern management of this condition and the generally accepted surgical treatment strategies must be discussed.…”
Section: Introductionmentioning
confidence: 99%